A comprehensive study on the mechanism behind formation and depletion of Cu2ZnSnS4 (CZTS) phases1. Issue 36 (28th September 2015) - Ahmad, Rameez; Brandl, Marco; Distaso, Monica; Herre, Patrick; Spiecker, Erdmann; Hock, Rainer; Peukert, Wolfgang
<x xml:space="preserve">Abstract</x> High efficiency kesterite based solar cells have vigorously raised the research interests in this material.